Question
upstudy study bank question image url

1) \( 2 x^{4}+9 x^{2}-68=0 \) 2) \( 18 x^{2}-2=0 \) \( 2-3 x \quad 3+2 x \)

Ask by Craig Adkins. in Spain
Feb 24,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Las soluciones son: 1) \( x = -2 \) y \( x = 2 \) 2) \( x = -\frac{1}{3} \) y \( x = \frac{1}{3} \)

Solution

Solve the equation \( 2x^4+9x^2-68=0 \). Solve the equation by following steps: - step0: Solve for \(x\): \(2x^{4}+9x^{2}-68=0\) - step1: Factor the expression: \(\left(x-2\right)\left(x+2\right)\left(2x^{2}+17\right)=0\) - step2: Separate into possible cases: \(\begin{align}&x-2=0\\&x+2=0\\&2x^{2}+17=0\end{align}\) - step3: Solve the equation: \(\begin{align}&x=2\\&x=-2\\&x \notin \mathbb{R}\end{align}\) - step4: Find the union: \(\begin{align}&x=2\\&x=-2\end{align}\) - step5: Rewrite: \(x_{1}=-2,x_{2}=2\) Solve the equation \( 18x^2-2=0 \). Solve the quadratic equation by following steps: - step0: Solve using square roots: \(18x^{2}-2=0\) - step1: Add or subtract both sides: \(18x^{2}=2\) - step2: Divide both sides: \(\frac{18x^{2}}{18}=\frac{2}{18}\) - step3: Divide the numbers: \(x^{2}=\frac{1}{9}\) - step4: Simplify the expression: \(x=\pm \sqrt{\frac{1}{9}}\) - step5: Simplify the expression: \(x=\pm \frac{1}{3}\) - step6: Separate into possible cases: \(\begin{align}&x=\frac{1}{3}\\&x=-\frac{1}{3}\end{align}\) - step7: Rewrite: \(x_{1}=-\frac{1}{3},x_{2}=\frac{1}{3}\) Las soluciones de las ecuaciones dadas son: 1) \( 2x^4+9x^2-68=0 \) tiene soluciones \( x=-2 \) y \( x=2 \). 2) \( 18x^2-2=0 \) tiene soluciones \( x=-\frac{1}{3} \) y \( x=\frac{1}{3} \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To tackle the first equation, \( 2 x^{4}+9 x^{2}-68=0 \), let’s make a substitution to simplify it! If we let \( y = x^2 \), then the equation transforms into a quadratic: \( 2y^2 + 9y - 68 = 0 \). By applying the quadratic formula, \( y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \), you can find the values of \( y \) and revert back to \( x \). Moving on to the second one, \( 18 x^{2}-2=0 \) is much simpler. Just add 2 to both sides, divide by 18, and then take the square root! You’ll find stunning results for \( x \) as \( \pm \sqrt{\frac{1}{9}} \) or \( \pm \frac{1}{3} \). For the expressions \( 2-3 x \) and \( 3+2 x \), they can take on different meanings based on the context, like function outputs or even settings for systems of equations. But both lead to valuable insights in everyday problems or modeling situations, adding to the fun of algebra!

Related Questions

ISCELÁNEA cribir, por simple inspección, el resultado de: \( \begin{array}{lll}(x+2)^{2} & \text { 14. }(x+y+1)(x-y-1) & \text { 27. }\left(2 a^{3}-5 b^{4}\right)^{2} \\ (x+2)(x+3) & \text { 15. }(1-a)(a+1) & \text { 28. }\left(a^{3}+12\right)\left(a^{3}-15\right) \\ (x+1)(x-1) & \text { 16. }(m-8)(m+12) & \text { 29. }\left(m^{2}-m+n\right)\left(n+m+m^{2}\right) \\ (x-1)^{2} & \text { 17. }\left(x^{2}-1\right)\left(x^{2}+3\right) & \text { 30. }\left(x^{4}+7\right)\left(x^{4}-11\right) \\ (n+3)(n+5) & \text { 18. }\left(x^{3}+6\right)\left(x^{3}-8\right) & \text { 31. }(11-a b)^{2} \\ (m-3)(m+3) & \text { 19. }\left(5 x^{3}+6 m^{4}\right)^{2} & \text { 32. }\left(x^{2} y^{3}-8\right)\left(x^{2} y^{3}+6\right) \\ (a+b-1)(a+b+1) & \text { 20. }\left(x^{4}-2\right)\left(x^{4}+5\right) & \text { 33. }(a+b)(a-b)\left(a^{2}-b^{2}\right) \\ (1+b)^{3} & \text { 21. }(1-a+b)(b-a-1) & \text { 34. }(x+1)(x-1)\left(x^{2}-2\right) \\ \left(a^{2}+4\right)\left(a^{2}-4\right) & \text { 22. }\left(a^{x}+b^{n}\right)\left(a^{x}-b^{n}\right) & \text { 35. }(a+3)\left(a^{2}+9\right)(a-3) \\ \left(3 a b-5 x^{2}\right)^{2} & \text { 23. }\left(x^{a+1}-8\right)\left(x^{a+1}+9\right) & \text { 36. }(x+5)(x-5)\left(x^{2}+1\right) \\ (a b+3)(3-a b) & \text { 24. }\left(a^{2} b^{2}+c^{2}\right)\left(a^{2} b^{2}-c^{2}\right) & \text { 37. }(a+1)(a-1)(a+2)(a-2) \\ (1-4 a x)^{2} & \text { 25. }(2 a+x)^{3} & \text { 36. }\left(x^{2}-11\right)\left(x^{2}-2\right)\end{array} \) \( \left(a^{2}+8\right)\left(a^{2}-7\right) \)
Algebra Mexico Feb 26, 2025
Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy